Informal work and how to measure it: A formal consensus at the 100th International Conference of Labour Statisticians - Grant Belchamber; Sylvain Schetagne (Global Labour University - Freunde und Förderer e.V., 2024)
Over the past fifty years, interest in and analysis of informality at work has burgeoned. Informal employment, including but not limited to un-declared work, is a core concern for unions worldwide. In 2019, nearly 2 billion workers (about 6 in every 10) were in informal employment. Informal employment is found in all countries, but its prevalence is inversely proportional to income being highest in low income countries at around 90 per cent of total employment, and lowest in high-income countries at less than 20 per cent of total employment. The share of women in informal employment exceeds that of men in most countries.1 Statistics on informal employment are vital for describing the structure and extent of informal employment. They are essential to identify groups of persons in employment most represented and at risk of informality, and to provide information on exposure to economic and personal risks, decent work deficits and working conditions. For unionists and policy makers, there is a need to measure the prevalence of informality across jobs, economic units and activities; the distribution of informal and formal jobs by socio-demographic characteristics; the percentage of persons with informal main jobs in the informal and formal sectors; levels of protection for those in informal and formal employment; and contextual vulnerabilities, including poverty, inequalities, discrimination, access to land and natural resources, household composition, access to social protection. These data provide the evidentiary base to push for and implement policies that can improve the working lives of those in informal employment. (...)
Keywords: 330